2017
DOI: 10.1136/emermed-2017-206717
|View full text |Cite
|
Sign up to set email alerts
|

Ionised calcium levels in major trauma patients who received blood en route to a military medical treatment facility

Abstract: Trauma patients who received blood products were at high risk of hypocalcaemia. Aggressive management of these patients with intravenous calcium during transfusion may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Additionally, current massive transfusion protocols dictate transfusion of high ratios of FFP [29] which has also been independently associated with hypocalcaemia [10, 30,31]. We therefore hypothesize that patients with admission ionized hypocalcaemia as observed in this study are likely to become more severely hypocalcaemic during haemostatic resuscitation [25,26].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Additionally, current massive transfusion protocols dictate transfusion of high ratios of FFP [29] which has also been independently associated with hypocalcaemia [10, 30,31]. We therefore hypothesize that patients with admission ionized hypocalcaemia as observed in this study are likely to become more severely hypocalcaemic during haemostatic resuscitation [25,26].…”
Section: Discussionmentioning
confidence: 81%
“…Hypocalcaemia was associated with early death mirroring the pattern of death observed in the setting of acute traumatic coagulopathy [23,24]. Early resuscitative measures involving blood transfusion are also likely to further exacerbate hypocalcaemia [25,26].…”
Section: Discussionmentioning
confidence: 84%
“…1 Previous civilian and military studies have shown that hypocalcemia (iCa <1.12) commonly occurs in trauma patients who receive even a small volume of blood products. 2,3 Recently published data demonstrated that the prevalence of hypocalcemia (iCa <1.12 mmol/L) in massively transfused patients was 97% and severe hypocalcemia (iCa < 0.9 mmol/L) was a significant risk factor for mortality. 4 Extreme ionized hypocalcemia (iCa < 0.8 mmol/L) is an independent predictor of mortality in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite using citrate, a well‐known calcium chelator, to preserve blood products for over 100 years, the data behind transfusion‐induced hypocalcemia are lacking 1 . Previous civilian and military studies have shown that hypocalcemia (iCa <1.12) commonly occurs in trauma patients who receive even a small volume of blood products 2, 3 . Recently published data demonstrated that the prevalence of hypocalcemia (iCa <1.12 mmol/L) in massively transfused patients was 97% and severe hypocalcemia (iCa < 0.9 mmol/L) was a significant risk factor for mortality 4 …”
Section: Introductionmentioning
confidence: 99%
“…Calcium levels have been proposed as important in the development of coagulopathy in the trauma patient with hemorrhagic shock. [27][28][29][30][31][32] Low ionized calcium levels are associated with hypotension, coagulopathy, and increased mortality. In particular, platelet dysfunction has been linked to hypocalcemia.…”
mentioning
confidence: 99%